2012
DOI: 10.1111/j.1467-8667.2012.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of an Industry Foundation Classes‐Based Graphic Information Model for Virtual Construction

Abstract: Virtual Construction (VC) applications encounter difficulty in sharing and exchanging information with one another due to the long periods of interoperability limitation. To address these issues, an Industrial Foundation Classes-based graphic information model (IFC-GIM) is developed according to the exchange requirement of VC, and using the representations of three models in the IFC schema and its extension by defining the dynamic property set and properties for animation. The three models include the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 25 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…As opposed to the CityGML standard, the IFC standard is not defined as a UML or XML schema. Instead, the model is specified using the data modeling language EXPRESS, which forms part of the ISO standard 10303 “STEP – Standard for the exchange of product model data.” Other import particularities of the IFC model are the comprehensive use of objectified relationships and inverse attributes (Eastman, ; Yang and Eastman, ; Zhang et al., ). The model is very fine‐grained and provides more than 600 entities for the detailed description of the semantics and the geometry of buildings and building components.…”
Section: A Multi‐scale Shield‐tunnel Product Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to the CityGML standard, the IFC standard is not defined as a UML or XML schema. Instead, the model is specified using the data modeling language EXPRESS, which forms part of the ISO standard 10303 “STEP – Standard for the exchange of product model data.” Other import particularities of the IFC model are the comprehensive use of objectified relationships and inverse attributes (Eastman, ; Yang and Eastman, ; Zhang et al., ). The model is very fine‐grained and provides more than 600 entities for the detailed description of the semantics and the geometry of buildings and building components.…”
Section: A Multi‐scale Shield‐tunnel Product Modelmentioning
confidence: 99%
“…Thus, a semantic object can be associated with multiple geometric representations (2D, 3D, BRep, CSG, etc.) (Zhang et al., ). This would, in principle, facilitate multi‐scale modeling providing different LoDs in the geometric part.…”
Section: A Multi‐scale Shield‐tunnel Product Modelmentioning
confidence: 99%
“…This educational virtual construction environment was used to help students develop their decision-making skills. Zhang et al (2012) indicated that physical objects, construction information, and process animation are essential elements in a practical 3-D virtual construction system designed to aid planners. As is clearly evident from these related research works, virtual construction has multiple applications in construction management.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Adequate standards, e.g. Industry Foundation Classes (IFC), have the potential of solving the problem of interoperability of software and representation of information in designing [15].…”
Section: Introductionmentioning
confidence: 99%